Using detergent-enhanced LAMP for African trypanosome detection in human cerebrospinal fluid and implications for disease staging. - Dennis J Grab; Olga V Nikolskaia; Bertrand Courtioux; Oriel M M Thekisoe; Stefan Magez; Maxim Bogorad; J Stephen Dumler; Sylvie Bisser (Public Library of Science (PLoS), 2019)
Objective Where human African trypanosomiasis (HAT) patients are seen, failure to microscopically diagnose infections by Trypanosoma brucei gambiense in blood smears and/or cerebrospinal fluid (CSF) in the critical early stages of the disease is the single most important factor in treatment failure, a result of delayed treatment onset or its absence. We hypothesized that the enhanced sensitivity of detergent-enhanced loop-mediated isothermal amplification (LAMP) will allow for point of care (POC) detection of African trypanosomes in the CSF of HAT patients where the probability for detecting a single parasite or parasite DNA molecule in 1 μL of CSF sample is negligible by current methods. Methodology We used LAMP targeting the multicopy pan-T. brucei repetitive insertion mobile element (RIME LAMP) and the Trypanosoma brucei gambiense 5.8S rRNA-internal transcribed spacer 2 gene (TBG1 LAMP). We tested 1 μL out of 20 μL sham or Triton X-100 treated CSFs from 73 stage-1 and 77 stage-2 HAT patients from the Central African Republic and 100 CSF negative controls. Results Under sham conditions, parasite DNA was detected by RIME and TBG1 LAMP in 1.4% of the stage-1 and stage-2 gambiense HAT CSF samples tested. After sample incubation with detergent, the number of LAMP parasite positive stage-2 CSF's increased to 26%, a value which included the 2 of the 4 CSF samples where trypanosomes were identified microscopically. Unexpected was the 41% increase in parasite positive stage-1 CSF's detected by LAMP. Cohen's kappa coefficients for RIME versus TBG1 LAMP of 0.92 (95%CI: 0.82-1.00) for stage-1 and 0.90 (95%CI: 0.80-1.00) for stage-2 reflected a high level of agreement between the data sets indicating that the results were not due to amplicon contamination, data confirmed in χ2 tests (p<0.001) and Fisher's exact probability test (p = 4.7e-13). Conclusion This study detected genomic trypanosome DNA in the CSF independent of the HAT stage and may be consistent with early CNS entry and other scenarios that identify critical knowledge gaps for future studies. Detergent-enhanced LAMP could be applicable for non-invasive African trypanosome detection in human skin and saliva or as an epidemiologic tool for the determination of human (or animal) African trypanosome prevalence in areas where chronically low parasitemias are present.